Placement of Labcor Pulmonary Conduit Results in a High Incidence of Postoperative Fever. Issue 1 (January 2021) - Shaker, Rouba; Arabi, Mariam; Khafaja, Sarah; Fayad, Danielle; Casals, Aia Assaf; Lteif, Mireille; Shamseddine, Sarah; Taqa, Mohammad Abu; Charafeddine, Fatmeh; Rassi, Issam El; Al-Halees, Zoheir; Bitar, Fadi; et al.
Background: Fever in the postoperative period in cardiac patients is common. The purpose of this study is to recognize the risk factors for prolonged postoperative fever in cardiac patients with pulmonary conduit insertion. Methods: Patients were identified retrospectively by looking at the International Classification of Diseases, Ninth Revision, Clinical Modification procedure code for pulmonary conduit insertion between June 2009 and December 2015 at the American University of Beirut Medical Center. Data about preoperative, perioperative, and postoperative variables were collected. Data entry and analysis were performed using SPSS version 22. Results: The study identified 59 patients. The most common type of pulmonary conduit used was the Contegra type (57.6%) (n = 34), followed by the Labcor type (20.3%; n = 12). Postoperative fever occurred in 61% of patients (n = 36). Fourteen patients (38.8%) had a prolonged fever that lasted for more than seven days. Prolonged postoperative fever was significantly associated with the Labcor pulmonary conduit ( P value < .001) and a longer duration of pacing wires ( P value: .039). Significantly prolonged fever that lasted for more than 21 days occurred in five patients who all had inserted the Labcor pulmonary conduit. Conclusions: The Labcor pulmonary conduit type is a risk factor for prolonged postoperative fever. The protracted use of pacing wires could be a consequence of the prolonged fever rather than a cause. In the absence of a demonstrable infectious etiology for prolonged postoperative fever in cardiac patients with pulmonary conduit insertion, the Labcor pulmonary conduit could be the underlying cause. Alternative management of such cases may lead to decreased antibiotic use and morbidity.